Atherogenic risk factors among preschool children in Crete, Greece - Hatzis, Christos M. (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: To investigate the presence of atherogenic factors among preschool children of Crete, Greece. MATERIALS AND METHODS: This was a cross-sectional study. The study population included 1189 children, aged four to seven years, examined from January to May 2005, in public kindergartens. Biochemical, anthropometric, and blood pressure measurements were performed. RESULTS: Of the boys 27.4% were classified as overweight or obese (obese 10.8%). The respective percentage for girls was 28.5% (obese 9%); 7.4% percent of the boys and 7.9% of the girls had blood pressure above the ninety-fifth percentile. TC of > 200 mg / dl was found in 14.4% and LDL-C of > 130 mg / dl in 13.8% of the children. Children with serum TG of > 100 mg / dl had a significantly higher mean WC and BMI than those with triglyceride levels of ≤ 80 mg / dl (59.7 vs. 55.9 cm and 17.9 vs. 16.6 kg / m(2); P < 0.05). Similarly, children with HDL-C < 45 mg / dl had significantly higher WC and BMI than children with HDL-C ≥ 60 mg / dl (57.7 vs. 53.5 cm and 17.1 vs. 16.5 kg / m(2); P < 0.05). Obese children had an Odds Ratio of 2.87 (95% confidence interval, 1.05 − 7.85, P = 0.041) for hypertriglyceridemia, as compared to non-obese children. CONCLUSION: Levels of obesity and especially central obesity were strongly related to other atherogenic risk factors in Cretan preschool children indicating the presence of this major public health problem in early ages.